Novel Combination Therapy: Monensin Potentiates Erlotinib-Induced Cytotoxicity - Khalil, Dayekh (Université d'Ottawa / University of Ottawa, 2013)
Receptor Tyrosine Kinase (RTK) inhibitors, such as erlotinib/tarceva, have been introduced in the past decade as a promising therapeutic option in Head and Neck Squamous Cell Carcinoma (HNSCC), however, they lack significant efficacy as single agents. As a result, RTK inhibitors require a combination based therapeutic approach with other treatment modalities. To uncover such a combination of agents, we performed a high throughput Prestwick library screen that included 1200 compounds approved by the FDA on HNSCC cell lines and found that monensin, a coccidial antibiotic, synergistically enhanced the cytotoxicity of erlotinib. RT-PCR revealed that monensin induced the expression of Activation of Transcription Factor (ATF) 3 and its downstream target C/EBP homologous protein (CHOP) which are key regulators of apoptosis. Furthermore, RNA-Seq analysis suggests that monensin augments erlotinib cytotoxicity by disturbing lipid and sterol biosynthesis. Therefore, identifying the mechanism of action exerted by monensin may open alternative avenues of cancer treatment.
Keywords: monensin; erlotinib; lovastatin; head and neck squamous cell carcinoma; combination treatment